Faktor - Faktor Yang Berhubungan Dengan Kepatuhan Perawat Rawat Inap Dalam Pelaksanaan Five Moments dan Hand Hygiene - Dian Matsyiwati Putri Sari; Ahmad Rizal; Sancka Stella G. Sihura (Lembaga Pengembangan Kinerja Dosen, 2024)
. Introduction: Nurses have a high risk of transmitting pathogens through their hands, because nurses spend the longest time with patients. Apart from this, a nurse must be able to comply with predetermined nursing duties and ethics, including